Analysis of the impact of dam slope modifications on the sensitivity to rapid drawdown, earthquakes, and changes in water level at the Jragung Dam in Semarang Regency - Rizal Undityo Rahardani; Trihanyndio Rendy Satrya (Jurnal Indonesia Sosial Teknologi, 2024)
Urugan-type dams are the most common type of dam to work on in Indonesia, with a material composition that is easy to obtain and relatively more economical. Based on the results of slope stability, a sensitivity analysis will be carried out based on changes in slope slope to post-construction conditions, during reservoir operation water level and rapid drawdown conditions. In this study, we will analyze the changes in the value of safety factors that occur on the slope of the body of the Jragung Dam due to rapid drawdown events and seismicities (OBE and MDE) using the help of seepage analysis calculation software and slope stability. There are three models used, namely Model 1 using geometry according to DED (slope of upstream slope 1: 3.0 and slope of downstream slope 1: 2.5), Model 2 of using modification of field construction geometry (slope of upstream slope 1: 2.5 and slope of downstream slope 1: 2.5), Model 3 of using modification of field construction geometry (slope of upstream slope 1: 2.5 and slope of downstream slope 1: 2,25). From the three models, the initial stage will be processed to find the phreatic line on the dam body when drawdown and the next stage to find the value of the dam slope safety factor. After the overall analysis was carried out both in terms of seepage analysis and stability analysis of the three simulation models, for the construction in the field on the Jragung dam, the 3rd Model can be used, namely the proposed geometric modification with an upstream slope of 1: 2.5 and a downstream slope of 1: 2.25, and material parameters according to the availability specifications at the work site. Regarding the stability of the slope, it is noted that at the time of the MDE earthquake load of 10,000 years, when the rapid-drawdown conditions y/h = 0.5h and y/h = 0.75h there is a possibility that the Jragung dam will be damaged, but not collapsed.